The Mollusca of Galicia Bank (NE Atlantic Ocean) - Gofas, Serge; Luque, Ángel A.; Oliver, Joan Daniel; Templado, José; Serrano, Alberto (European Journal of Taxonomy, 2021)
An illustrated checklist of the Mollusca of Galicia Bank, a large and deep seamount off the NW Iberian Peninsula, is provided. The studied material was collected in 8 samples of Seamount 1 cruise (1987), 7 samples of ECOMARG 0709 (2009) and 36 samples of BANGAL 0711 (2011), between 615 and 1768 m. A total of 212 species are known to occur at the Galicia Bank (1 Monoplacophora, 7 Solenogastres, 3 Polyplacophora, 132 Gastropoda, 54 Bivalvia, 6 Scaphopoda, and 9 Cephalopoda), 21 of which from previous studies only. Four species are described as new, 34 species are first record in Spanish waters and another 20 species first record for the Northern Spanish waters. Over 7500 specimens, representing 104 species, were collected alive, and 87 species were represented by empty shells only. Only 53 species were detected in both Seamount 1 and BANGAL 0711; most of the species are rare and more species can be expected if exploration is continued. There is a marked difference in species composition between the summit platform (615‒1000 m) and the deeper part below 1500 m, with some genera (e.g., Colus and Limopsis) represented by alternative species. Endemism, if any, is very low and most of the species are widespread.